A comparison of some egg geometry parameters in four close-bred stocks of Japanese quail - Lohani, F.; Ahmad, S. (Scientific Journal of Zoology, 2013)
Present study was conducted to evaluate some egg geometry parameters infour close-bred stocks Major [(M), Kaleem (K), Saadat (S) and Zahid (Z)] ofJapanese quail at Avian Research and Training Centre UVAS, Lahore. For thispurpose, 144 eggs (36 eggs from each CBS) were subjected to egg geometryparameters (shape index, surface area and volume). Statistical analysisaccording to CRD with one way ANOVA technique, comparison of mean by using DMRtest with the help of SAS 9.1 revealed significant differences among fourclose-bred stocks regarding surface area and volume. However, shape indexremained non-significant.